Colombian overview of breast, cervix and prostate cancer - Solano-Dazzarola, Paola Andrea (2023)
Introduction: Cancer incidence is 57% in underdeveloped countries, with breast, cervix, and prostate cancers leading the main causes of death in countries such as Colombia where cases are increasing despite efforts to mitigate this problem. Objective: To recognize the behavior of breast, cervix, and prostate cancer in the last decade according to sociodemographic factors in Colombia. Methods: An advanced search was performed in Embase (Elsevier) obtaining 36 documents, in addition to consulting data from national and international organizations. Results: The growth curve is related to socioeconomic factors, lifestyles, educational level, and healthcare conditions Conclusions: Health institutions and epidemiological surveillance must improve the processes of detection, timely treatment, and follow-up of patients with suspected and confirmed cancer, as well as reinforce disease prevention and promotion strategies.